2011
DOI: 10.1128/mcb.05516-11
|View full text |Cite
|
Sign up to set email alerts
|

CrbpI Modulates Glucose Homeostasis and Pancreas 9-cis-Retinoic Acid Concentrations

Abstract: Cellular retinol-binding protein type I (CrbpI), encoded by Rpb1, serves as a chaperone of retinol homeostasis, but its physiological effects remain incompletely understood. We show here that the Rbp1 ؊/؊ mouse has disrupted retinoid homeostasis in multiple tissues, with abnormally high 9-cis-retinoic acid (9cRA), a pancreas autacoid that attenuates glucose-stimulated insulin secretion. The Rbp1 ؊/؊ pancreas has increased retinol and intense ectopic expression of Rpb2 mRNA, which encodes CrbpII: both would con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 52 publications
(63 reference statements)
9
44
0
Order By: Relevance
“…A study of Rbp1 −/− mice, which lack CRBPI, by Kane et al confirmed the importance of CRBPI in glucose homeostasis (82). Rbp1 −/− mice fed a diet providing a relatively large amount of retinol (30 IU/g of diet) showed abnormally elevated pancreatic 9cRA levels and low insulin levels in the fed state, hyperglycemia, and marked glucose intolerance.…”
Section: Retinoids In Pancreatic Islet Biologymentioning
confidence: 88%
“…A study of Rbp1 −/− mice, which lack CRBPI, by Kane et al confirmed the importance of CRBPI in glucose homeostasis (82). Rbp1 −/− mice fed a diet providing a relatively large amount of retinol (30 IU/g of diet) showed abnormally elevated pancreatic 9cRA levels and low insulin levels in the fed state, hyperglycemia, and marked glucose intolerance.…”
Section: Retinoids In Pancreatic Islet Biologymentioning
confidence: 88%
“…Retinoids, and the enzymes that control retinoid formation, represent a complex, highly regulated system that controls fundamental biological processes, including fuel metabolism 15,17,21 . We previously reported that mice lacking Aldh1a1 , the rate-limiting enzyme in Rald conversion to retinoic acid, show enhanced energy expenditure when fed a high-fat diet 16 , suggesting that they have altered BAT activity.…”
Section: Discussionmentioning
confidence: 99%
“…To be consistent with the nutritional requirements of the mice with an RBP knockout background, which represents the majority of the genetically modified strains in our colony, we fed our mice a diet containing vitamin A levels higher than those recommended (29). Other laboratories use a similar concentration of vitamin A in the mouse diet and define this diet as "copious in vitamin A" (30). Furthermore, note that the diet used in this study was different (same manufacturer, different product) from the diets used in previously published papers from our laboratory.…”
Section: Methodsmentioning
confidence: 95%